ISOLATION OF POTENTIALLY PATHOGENIC BACTERIA FROM THE INTERNAL SUDANESE COASTAL WATERS OF PORT SUDAN - Omer Abdalla, Ehab; Taha Abdalla Shigidi , Mohammed (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to isolate and identify some species of opportunistic pathogenic bacteria that may be present in the inner Sudanese coastal waters of Port Sudan (Khour Salalab). From this area, 10 sea water samples were collected and used for isolation and identification of possible potentially pathogenic bacteria which increases the chances of the presence of frank pathogens. Water samples were inoculated in Selenite broth and after an incubation period of 48hrs at 37ºC, streaked onto MacConkey’s and Salmonella-Shigella agar then the pure colonies were picked and identified. A variety of opportunistic pathogens were isolated which were: Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Citrobacter freundii, Pseudomonas aeruginosa, Pseudomonas alcaligenis, Pseudomonas fluoresens, Streptococcus faecalis and Vibrio anguillarum and this increases the possibility of the presence of frank pathogens. The study showed that more efforts should be made to reduce marine pollution and improve water sources management and a need for strategy to improve general and environmental health. there are no records about the number of swimmers and swimming-related diseases in this area. However, due to the develop of tourism and its related activities, chances of swimming related diseases are likely to increase.